PBG 7. Diallel analysis of six elite open-pollinated maize varieties (The Philippine Journal of Crop Science, 2018)
Diallel is one of the most popular mating designs in maize breeding, generating substantial genetic information when properly implemented and analyzed. This study was conducted to assess the heterotic relationships of six elite open-pollinated maize varieties from IPB which is the initial strategy in creating heterotic groups between native maize populations collected from the philippines. Diallel crosses were generated during Dry Season 2016 and planted in multi-location trials during Wet Season 2017 following a Randomized Complete Block Design. Variability on grain yield and agronomic traits was observed in each trial location and combined ANOVA was done after the homogeneity of variance test. Griffing Method IV analysis revealed significant differences among crosses and crosses x location interaction. SCA x location effects was significant as well as GCA effects, while GCA x location and SCA effects were not significant. IPB Var 13 exhibited the highest positive GCA estimate while Pop 62 had the most negative estimate. Using the combining ability matrix, GGE Biplot and Cluster analyses revealed relationships of the six parents representing around 65% of the variation in grain yield. Aside from demonstrating heterotic response of the parents, our results present the possibility and opportunity of choosing appropriate broad-base testers to group native maize populations from the Philippines into useful heterotic groups. Inbred testers may be used to further refine the proposed heterotic grouping.